Sistem Pakar Diagnosa Kecanduan Game Online dengan Metode Certainty Factor dan Euclidean Distance Berbasis Web - Setyawan, Zaini Agus (JDMIS: Journal of Data Mining and Information Systems, 2023)
The phenomenon of addiction in playing online games is very serious and requires early prevention. Addiction to online games if it is late in handling it has a negative impact on everyday life. Based on these problems, an expert system is needed to diagnose the level of online game addiction based on the symptoms experienced. This study aims to determine the level of addiction by analyzing data using the Certainty Factor method, which is a method for managing uncertainty in a rule-based system. Meanwhile, the use of the Euclidean Distance method aims to determine the shortest distance between two data, in designing the system using XAMPP as a local server that provides the PHP programming language and phpMyAdmin to manage the MySQL database. The method used is the RAD (Rapid Application Development) method. Testing using black-box testing results shows that the function of the system can run well as a whole. This research produced output in the form of an Expert System for Diagnosing Online Game Addiction Symptoms with the Certainty Factor Method and Web-Based Euclidean Distance where this website is expected to make it easier for users or online game players to diagnose the level of addiction in playing online games.